Lifestyle Modifications to Help Prevent Headache at a Developmental Age - Raucci, Umberto; Boni, Alessandra; Evangelisti, Melania; Della Vecchia, Nicoletta; Velardi, Margherita; Ursitti, Fabiana; Terrin, Gianluca; Di Nardo, Giovanni; Reale, Antonino; Villani, Alberto; Parisi, Pasquale (Frontiers in Neurology, 2021)
Headache is the world’s seventh most significant cause of disability-adjusted-life years in people between 10-14 years old and its management is based on pharmacological approach and lifestyle recommendations. Many studies show the association between each migraine lifestyle and behaviors triggers and frequency and intensity of headache; nevertheless, to our knowledge, there is lack of evidence in literature on the overall aspects of this topic. The role of lifestyle advice in pediatric migraine is central, in particular as an educational promotion that starts in childhood to improve quality of life of future adult migraine patients, to avoid headache chronification and increasing wellbeing. This data is even more important, given the scarce scientific evidence available on drug therapy for prophylaxis in developmental age. In fact, data in literature suggest that “lifestyle recommendations” are perfect balance to regular sleep and meal, adequate hydration, limited consumption of caffeine, smoking and alcohol, regular physical activities to avoid overweight and stressors. Moreover, a new therapeutic strategy for the control of headache in adults is the use of the ketogenic diet, enhancing the possible role of dietary factors, although, more studies should be done especially among children and adolescent. It is particular important to improve lifestyle advices as central role of pediatric headache management and also to reduce chronification and to increase wellbeing in future adulthood of patients. This review highlights how the various aspects of daily life can lead to improved changes in headache in developmental age.